Lithostratigraphy and microfacies analysis of Avanah Formation (Middle Eocene) in Gomaspan section northeast Erbil City, Iraqi Kurdistan region: DOI: 10.48129/kjs.11183 - Asaad, Irfan Sh (Kuwait Journal of Science, 2022)
Lithostratigraphy and microfacies analysis of the Avanah Formation (Middle Eocene) were studied in the Gomaspan section in the Bina Bawi anticline, northeast of Erbil city, Iraqi Kurdistan region. The formation comprises of 56 m of medium to thick bedded yellow limestone, grey dolomitic limestone and blue marly dolomitic limestone interbedded with thin beds of blue marl and dark grey shale with interval of sandy limestone in the middle part and thin to medium bedded limestone interbedded with red mudstone. The petrographic study of 29 thin sections of Avanah carbonates revealed that the majority of matrix are carbonate mud (micrite) with few microspar. The skeletal grains include benthonic foraminifera, dasycladacean green algae, ostracods, calcisphers, pelysepods, rare planktonic foraminifera and bryozoa in addition to bioclasts. Non-skeletal grains encompass peloids, oncoids, intraclasts and extraclasts with common monocrystalline quartz. Based on field observation and petrographic analysis, three different lithostratigraphic units were identified. They are in ascending order: A-Thick bedded dolomitic marly limestone interbedded with shale. B- Bedded dolomitic limestone interbedded with shale and marl. C- Thin to medium bedded limestone interbedded with red mudstone. Depending on detailed microfacies analysis of carbonate rocks, three main microfacies and 12 submicrofacies are recognized. From the sum of all petrographic, facies, textural analyses, it is concluded that Avanah Formation in Gomaspan section, was deposited at the shallow marine environment, semi restricted lagoon, in lower and upper parts and open lagoon environment in the interval in the middle part.